Phosphorus and Boron Response at Different Growth Stages in Tomato - Akhoundnejad, Yelderem; Küçük, Ragıp; Irmak, Seyyıd; Sevgin, Nevzat (My University, 2025)
The study was carried out during the 2019 growing season in Çığır Village of İdil District, Şırnak Province, using a Randomized Complete Block Design (RCBD) with three replications. Kamenta F1 tomato variety was used in the experiment. Phosphorus (0.125%, 0.25%, 0.5% and 1%) and boron (0.5, 1, 1.5 and 2.5 ppm) were applied on the leaves as fertilizers. Evaluation of Shoot (stem and leaves), number of flowers, chlorophyll content (SPAD) of leaves, measurement of fruit diameter and height, Brix and pH content in fruit juice, fruit yield, amount of titratable acid and P, K, Mg, Ca, Mn, Fe, Cu, Zn in stem and leaves and B concentration analyses were performed. As a result of the experiment, it was determined that the boron and phosphorus fertilizers applied at different times positively affected the Shoot (stem and leaves), Brix, pH, fruit yield and macro and micro elements content in the stem and leaves of the tomato plant. Pre-flowering applications of boron and phosphorus had differing effects on tomato plants. Overall, the most effective treatments were P3 (0.5%) for phosphorus and B3 (1.5 ppm) for boron. Boron applications applied before flowering had a more pronounced promotive effect on plant development compared to phosphorus.
Keywords: Solanum lycopersicum; Quality; Yield; Boron; Phosphorus